POF (paclitaxel/oxaliplatin/5-fluorouracil/leucovorin) vs. SOX/CAPOX/FOLFOX as a postoperative adjuvant chemotherapy for curatively resected stage III gastric cancer: Study protocol for a randomized controlled trial, FNF-014 trial - Su, Liyu; Zhao, Shen; Yin, Yi; Huang, Feng; Zhu, Jinfeng; Chen, Luchuan; , FNF Independent Investigations Group; Lin, Rongbo (Frontiers in Medicine, 2022)
Background: Postoperative chemotherapy is a standard treatment for stage II and III gastric cancer in Asia. With regard to single-agent or doublet, the need for improvement has consistently been pointed out because of the relatively poor outcome for patients with stage III gastric cancer. Triplet has shown significant survival benefits in the perioperative setting. We conducted a randomized, multicenter, phase III study to compare triplet to doublet regimens for patients with stage III gastric cancer. Methods: This is currently enrolling patients (n=230) with pathologic stage III gastric cancer after D2 lymph node dissection and achieved R0 resection. Patients are randomized 1:1 and stratified by tumor stage (IIIA, IIIB, or IIIC, AJCC 8th) into POF or SOX/CAPOX/FOLFOX. S-1 and oxaliplatin (SOX): oxaliplatin 130 mg/m2 on day 1, oral S-1 80-120mg/m2 divided by two on days 1 to 14 every 21 days for 8 cycles. Capecitabine and oxaliplatin (CAPOX): oxaliplatin 130 mg/m2 on day 1, oral capecitabine 1000 mg/m2 twice daily on days 1 to 14 every 21 days for 8 cycles. Folinic acid (or leucovorin), 5-fluorouracil and oxaliplatin (FOLFOX): oxaliplatin 85 mg/m2, levo-leucovorin 200 mg/m2, and 5-fluorouracil (5-FU) 400 mg/m2 bolus on day 1, then 5-FU 2400 mg/m2 continuous infusion over 46 hours, every 14 days for 12 cycles. Three doublets were chosen by the clinicians. Paclitaxel, oxaliplatin, 5-fluorouracil and leucovorin (POF): paclitaxel 135 mg/m2, followed by FOLFOX omitted 5-FU bolus, every 14 days for 12 cycles. The primary end point is 3-year disease-free survival (3-year-DFS). Secondary end points are overall survival (OS) and safety (any adverse event). Discussion: The results of this study will help establish postoperative clinical evidences for patients with locally advanced gastric adenocarcinoma or gastroesophageal junction adenocarcinoma. Trial registration: This clinical trial has been registered with ClinicalTrials.gov, registration number: NCT0378826. Registered on December 26, 2018.